Aerodynamic properties and flow behavior for a badminton shuttlecock with spin at high reynolds numbers - Nakagawa, K.; Hasegawa, H.; Murakami, M.; Obayashi, S. (Procedia Engineering, 2012)
The shuttlecock used in the game of badminton has astonishing aerodynamic characteristics. The shuttlecock which has an open conical shape is the smallest ballistic coefficient and exhibits the largest in-flight deceleration of any airborne sporting implement. The ballistic coefficient of a body is a measure of its ability to overcome air resistance in flight and is inversely proportional to the deceleration. To evaluate correctly the forces acting the shuttlecock, it is necessary to know the in-flight properties determined from the aerodynamics. The purpose of this study is to investigate the relationship between aerodynamic properties and flow fields for a shuttlecock with spin rotation at high Reynolds numbers. Particle image velocimetry (PIV) was used to aid in understanding the flow field in the near field of the shuttlecock edge for the wind tunnel test. The effect of shuttlecock deformation on aerodynamic properties was also investigated because it is presumed that aerodynamic forces are affected by the deformation of the shuttlecock skirt. The drag coefficient for the shuttlecock with no gap is significantly smaller than that for the ordinary shuttlecock (with gap). For the ordinary shuttlecock, the air flows through the gap in the shuttlecock skirt, and this flow is related to high aerodynamic drag. That is, the high aerodynamic drag of a badminton shuttlecock is causes by the gap in the shuttlecock skirt.